Urgensi Integritas Nasional Sebagai Persatuan Dan Kesatuan Bangsa - Farel Febriananda; Dwi Putri Lestari; Mitha Rafina; Sabrina Sabrina; Bambang Trisno (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Indonesia is a country with high diversity, both in terms of ethnicity, religion, culture and language. This diversity is the nation's wealth, but it can also be a potential for the emergence of division and conflict. Efforts to maintain national unity and unity are very important in the Indonesian context. National integrity is an important parameter in realizing national unity and integrity. The purpose of this writing is to understand the urgency of national integrity as national unity and integrity. By using the Literature review method, namely collecting library data and information by exploring knowledge or science from sources such as books, journals, written works, lecture notes and several other sources that are related to the research object. The research results show the importance of national integration: National integration is very important to build the unity and integrity of the Indonesian nation. This integration reflects an effort to combine various elements in society, including ethnicity, culture and religion, into one strong national entity. Preventing Internal Conflict: National integration plays an important role in preventing internal conflict that could threaten the integrity of the country. This integration helps reduce inequality and injustice, which are the roots of internal conflict. Building National Identity: National integration helps build and strengthen national identity. National identity is the basis for citizens' sense of pride in their country. Through integration, shared values, national symbols and shared history can be explored and promoted. Development of National Integration: National integration enables countries to provide better services and build national unity. This integration also helps raise awareness of a common identity, strengthen national identity, and build national unity.